2021
DOI: 10.3390/ijerph18158190
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Colorectal Cancer Screening Promotion Using E-Media Decision Aids: A Systematic Review and Meta-Analysis

Abstract: Colorectal cancer (CRC)-screening reduces mortality, yet remains underutilized. The use of electronic media (e-media) decision aids improves saliency and fosters informed decision-making. This systematic review aimed to determine the effectiveness of CRC-screening promotion, using e-media decision aids in primary healthcare (PHC) settings. Three databases (MEDLINE, Web of Science, and the Cochrane Library) were searched for eligible studies. Studies that evaluated e-media decision aids compared to usual care o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…While its high traffic and broad reach make it a potent channel for public health campaigns, healthcare providers must be mindful of its limitations in patient education. A meta-analysis revealed that videos and multimedia programs significantly encourage CRC screening, enhancing completion rates [ 38 ]. However, a study noted that while YouTube's CRC education videos are high in production quality, their accountability and content scores vary greatly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While its high traffic and broad reach make it a potent channel for public health campaigns, healthcare providers must be mindful of its limitations in patient education. A meta-analysis revealed that videos and multimedia programs significantly encourage CRC screening, enhancing completion rates [ 38 ]. However, a study noted that while YouTube's CRC education videos are high in production quality, their accountability and content scores vary greatly.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial for these videos to directly address the most prevalent questions and stigmas related to colorectal screening, ensuring that they are highly relevant and engaging. Health initiatives for CRC should aim to enhance understanding, alleviate fears and distrust, and promote CRC screening as a vital preventive measure, particularly focusing on older adults [ 38 ]. Employing pop-up ads with concise, catchy phrases that tackle common misconceptions or stigmas can significantly boost CRC screening awareness among the general population [ 40 ].…”
Section: Discussionmentioning
confidence: 99%